The Phenomenon of Illegal Street Racing Among Teenagers: A Criminological Study in the Jurisdiction of Pematangsiantar Police - Yudha Putra Tampubolon; Sarles Gultom; Desy Kartika C. Sitepu (KOLABORASI: Journal of Multidisciplinary, 2024)
Criminological Review of Illegal Racing by Teenagers in the Pematangsiantar Police Jurisdiction. This study aims to (1) determine the factors that cause illegal racing by teenagers in the Pematangsiantar Police jurisdiction. (2) To determine efforts to overcome illegal racing by teenagers in the Pematangsiantar Police jurisdiction. This study was conducted in the Pematangsiantar Police area, this study is a qualitative descriptive study. The types of data in this study are primary data and secondary data, with direct observation and interview data collection techniques. The results of the study indicate that the factors that cause teenagers to be involved in illegal racing are (1) not having someone as a role model in understanding and absorbing the values ​​or norms that apply in society, (2) Lack of supervision and concern for the community environment where the racing location occurs, (3) the activity is attractive as an alternative entertainment for some people (especially in cities that have a scarcity of alternative positive activities for the younger generation), (4) lack of police personnel so that perpetrators can freely carry out their activities. Pematangsiantar Police make efforts to overcome the problem including preventive efforts and repressive efforts. Preventive efforts or prevention, include socialization or counseling carried out by the Pematangsiantar Police to the community, conducting vehicle operations, and guarding posts prone to illegal racing. While repressive efforts or action, include following up on complaints from the community around the racing location who feel disturbed and police officers who have conducted a survey in advance in the illegal racing area, conducting control operations or raids, the perpetrators who are caught are then secured at the Pematangsiantar Police to seek information to find evidence, given a fine by confiscating those who are not equipped with STNK, SIM, driving safety and standardization eligibility, and for perpetrators who repeat illegal racing will be given guidance from the Pematangsiantar Police